Autism spectrum disorder characteristics, causes, and practical issues - Boucher, Jill; Boucher, Jill (Los Angeles SAGE, 2017)
What is meant by "autistic spectrum disorder" (ASD)? What behaviours do people with ASD share regardless of age, ability and individual differences: What causes ASD? Is ASD increasingly common? And are males more often affected than females? How may people with ASD best be helped to live fulfilling lives a valued members of society? Can ASD be - should it be - 'cured'? The updated and extensively revised 2nd edition of this popular book explores answers to these questions based on the latest developments in research and practice. Individual chapters summarise what is known about the 'first causes ' of ASD, their effects on the brain, and on psychological functioning. Other chapters summarise methods of assessment, treatment, education and support. Illustrated with real-life accounts of people with ASD and examples of current 'best practice', this book provides essential information in an accessible and lively form.
Historical background -- Current concept and definition -- The fuller picture: shared characteristics -- The fuller picture: sources of diversity -- Facts and figures: epidemiology and lifespan development -- A framework for explaining autism -- Root causes -- Brain bases -- Proximal causes 1: diagnostic behaviours -- Proximal causes 2: additional shared characteristics and major specifiers -- Assessment, diagnosis and screening -- Intervention -- Care.
Preceded by Autistic spectrum / Jill Boucher. 1st ed. 2009.
Includes bibliographical references and index.
Keywords: Autism